Sistem Pendukung Keputusan untuk Menentukan Hasil Bisnis Pujasera Terbaik dimasa Pandemi Covid 19 dengan Metode Fuzzy Tahani dan Simple Additive Weighting (SAW) berbasis Website (Studi Kasus: Pujasera Hangout Salihara) - Abdullah, Mohammad Aldinugroho; Fitri, Iskandar; Nathasia, Novi Dian (KITA Institut, 2021)
Pujasera Hangout Salihara is a company engaged in the business of serving food and beverages for the public. During the Covid 19 pandemic, there were many impacts, one of which was in the restaurant business sector. With the Fuzzy database method Tahani model and Simple Additive Weighting are used in determining the destination of the favorite food menu at the food court according to customer desires accurately, quickly, and easily understandable, helping the food court owner and tenant of the food court at the salihara hangout food court in providing food menu recommendations, the most popular drink menu and the highest and lowest rating of each food court in a week or a month. The method of Fuzzy database model Tahani and Simple Additive Weighting are applied in making a decision support system with stages determined by the researcher. The result of the Decision Support System is a system that can assist in making decisions that are carried out accurately and according to the desired goals. In applications that have been built, the results are based on the value of the degree of membership and the truth value of the calculation process in the application. Testing is done by means of the BlackBox testing.Keywords:Decision support system, Fuzzy database method, Tahani model, Simple Additive Weighting, Pujasera.